Perkembangan Dan Penerapan Theory Of Acceptance Model (TAM) Di Indonesia - Mainatul Ilmi; Fetri Setyo Liyundira; Afria Rachmawati; Deni Juliasari; Palupi Habsari (STIE Mandala Jember, 2020)
The article tellsabout model of technology acceptance. A system used by the end user necessary to test whether the system effectively and efficiently can be applied by user. Technology Acceptance Model (TAM) adopted the Theory of Reasoned Action (TRA) that is widely used to predict the acceptance and usefulness of the system information. TAM usesa comparison between the Theory of Reasoned Action (TRA) and the Theory of Planned Behavior (TPB). TAM is designed to predict the acceptance or use of information systems by usersand profit for a job. An acceptance of the theory of information systems began to be implemented in Indonesia from 2004 until today, which adopts the model proposed Davis et al in 1989. The theory was apparently accepted by the public to assess the acceptance of a system by the user based on its core construct perceived Ease of Use (PEOU) and perceived usefulness (PU). In Indonesia some researchers are implementing TAM 1989 at different locations, in various sectors as well as the time and different situations by using several different methods of analysis in each study. A significant result of variables in TAM lead this theory can be applied further in other information systems in Indonesia in addition to that already done the research for TAM is very easyto apply and be accepted by the public in a variety of sectors, namely in the public sector, business or private. Keywords: Technology Acceptance Model (TAM), perceived Ease of Use, perceived usefulness, system information